The Effectiveness of Using Peer Feedback on Students’ Writing Descriptive Text: The Effectiveness of Using Peer Feedback on Students’ Writing Descriptive Text - Rossawati wati (JEET, Journal of English Education and Technology, 2021)
This article aims to determine whether there is a significant difference in the writing skills of the tenth graders of SMA NU Centini before being taught using peer feedback and after being taught using peer feedback. This research is classified as pre-experimental research. Involving 20 student in one class by comparing student scores before being taught using peer feedback (pre-test) and after being taught using peer feedback (post-test The results showed that there was a significant difference in students writing skills before being given treatment and after being given treatment using peer feedback techniques. This can be seen in the results of hypothesis testing through the Paired Sample T-Test. The results of the analysis showed that the post-test mean score (60) was higher than the pre-test mean (42.25). So Ha is accepted. This means that there is an increase in students writing achievement after being given treatment. Furthermore, the researcher has calculated that the score tobtained > ttable (7.993 > 2.093) and significant 2-tailed < 0.05 (0.000 < 0.05). So, Ha accepted. This means that the Peer Feedback technique statistically has an influence on student abilities writing descriptive text.